DELINEASI CEKUNGAN BUSUR MUKA SIMEULUE BERDASARKAN DATA ANOMALI GAYA BERAT - Santi, Lauty Dwita; Setiadi, Imam; Panggabean, Hermes (Pusat Survei Geologi, 2010)
The study of hydrocarbon potential at the fore-arc basins of west offshore Sumatra has been done by many writers. Recently, Simeulue basin, has been put at the spotlight as the Germany's BGR research team published several latest seismic lines showing great sediment accumulation in this basin. Although many new information and speculation emerge by the result of that research, until now the exact basin boundary itself has never been discussed. Delineation process of Simeulue basin in this study is done by applying gravity anomaly data that covers a wide area enough to determine the apparent boundary of sediment distribution within the basin. A gravity anomaly profile is produced using forward modeling method, showing the geometry of the basin, with maximum length of 418 km. The northward and southward of this basin is bounded by hightopographies that separate Simeulue basin with the other adjacent basins.Keywords : Basin delineation, Gravity anomaly